Subjective Versus Objective Economic Measures. A fuzzy logic exercise - António Caleiro (Universidade de Évora, Departamento de Economia, 2003)
It is rather evident that there is much more (statistical) information about objective aggregates, such as inflation, output or unemployment than that concerning subjective aggregates, such as well-being, satisfaction, confidence or even expectations. Due to its characteristics, fuzzy logic can and should indeed be used to understand how some of those subjective measures can be approximated by objective ones. This task is accomplished in the paper by the use of Portuguese data on consumer confidence - the subjective economic measure - and on the unemployment rate - the objective economic measure -. The results clearly indicate that to be a worthwhile exercise as the clear importance of unemployment on confidence is only revealed by the fuzzy logic approximation.
hdl:10174/8397
Keywords: C10; C82; E32; 330; Confidence; Fuzzy Logic; Objective Measures; Subjective Measures